An overview of reactive hydride composite (RHC) for solid-state hydrogen storage materials. (8th September 2021) - Ali, N.A.; Sazelee, N.A.; Ismail, M.
Abstract: Hydrogen storage using the metal hydrides and complex hydrides is the most convenient method because it is safe, enables high hydrogen capacity and requires optimum operating condition. Metal hydrides and complex hydrides offer high gravimetric capacity that allows storage of large amounts of hydrogen. However, the high operating temperature and low reversibility hindered the practical implementation of the metal hydrides and complex hydrides. An approach of combining two or more hydrides, which are called reactive hydride composites (RHCs), was introduced to improve the performance of the metal hydrides and complex hydrides. The RHC system approach has significantly enhanced the hydrogen storage performance of the metal hydrides and complex hydrides by modifying the thermodynamics of the composite system through the metathesis reaction that occurred between the hydrides, hence enhancing the kinetic and reversibility performance of the composite system. In this paper, the overview of the RHC system was presented in detail. The challenges and perspectives of the RHC system are also discussed. This is the first review report on the RHC system for solid-state hydrogen storage. Highlights: Current progress in reactive hydride composite (RHC) for hydrogen storage is reviewed. Roles of intermediate compounds in RHC system is highlighted. Future perspectives and challenges of RHC as hydrogen storage medium are discussed.